Pembelajaran Daring: Perkembangan (Efektivitas dan Kekurangan) di Masa Pandemi Covid19 - Fathul Arif; Kaharuddin; Muhammad Irwan (IAIN PAREPARE, 2022)
Education from time to time always undergone changes, technological progress has become the biggest and greatest in this change. In essence, the presence of technology aims to facilitate human activities in the social, economis, and education fields. The use of technology in education has been carried out by many educators, none other than comments from teachers and lecturers. Varios aplication modes make it easier for teachers to design learning . The presence of Covid19 is certainly a concern for community, so the use of technology in learning the right alternative, best of course it will add new problems.